EXPLORING THE ROLE OF FORENSIC ACCOUNTING IN LAW ENFORCEMENT “A CASE STUDY FROM THE UK” - S. Mohamad, Idris (International Journal of Psychosocial Rehabilitation, 2020)
The rapid growth of forensic accounting, an area concerned with the prevention and detection of criminal activities, especially those of white-collar criminals and financial fraud, has been intensified by the law enforcement bodies in the United Kingdom. For the development and investment of a country, cracking down on white-collar criminals must be conducted. Forensic accounting, therefore, refers to the investigation of financial fraud through conducting the analysis of financial records aimed at proving or disproving the crimes and serving as the primary court witness in the jurisdiction. The term investigative accounting is also known to constitute the application of specific skills and knowledge in the identification of unauthentic transactions and evidence gathering of the frauds. The research objectives include determination of how forensic accounting enhances adherence to the law by the employees in their workplaces, how the organizational managers in the United Kingdom embrace forensic accounting in enhancing organizational accountability, and determination of the criteria followed by the law enforcement officers in ensuring that transparency is enhanced in different business fields. From the research conducted through interviews and case studies, it was discovered that forensic accounting plays a crucial role in enhancing law enforcement in the United Kingdom, with 698 business premises relying on forensic accounting to restore transparency and reduce corruption cases. More importantly, most of the senior forensic accountants heavily focused on the litigation support roles. It was also determined that the rate of financial fraud intensively decreased in 2017 to a rate of 5% due to improved forensic accounting through internal control.